2016
DOI: 10.1007/s10113-016-1002-7
|View full text |Cite
|
Sign up to set email alerts
|

A framework for habitat monitoring and climate change modelling: construction and validation of the Environmental Stratification of Estonia

Abstract: Environmental stratifications provide the framework for efficient surveillance and monitoring of biodiversity and ecological resources, as well as modelling exercises. An obstacle for agricultural landscape monitoring in Estonia has been the lack of a framework for the objective selection of monitoring sites. This paper describes the construction and testing of the Environmental Stratification of Estonia (ESE). Principal components analysis (PCA) was used to select the variables that capture the most amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…Geijzendorffer & Roche (2013) have shown that the GHCs are sufficiently robust to record habitats consistently. More recently Villoslada et al (2017) have carried out a similar procedure at a smaller scale in the 45,000 1 km squares in Estonia.…”
Section: The Potential Of Automated Habitat Mappingmentioning
confidence: 99%
“…Geijzendorffer & Roche (2013) have shown that the GHCs are sufficiently robust to record habitats consistently. More recently Villoslada et al (2017) have carried out a similar procedure at a smaller scale in the 45,000 1 km squares in Estonia.…”
Section: The Potential Of Automated Habitat Mappingmentioning
confidence: 99%
“…Моделювання екологічної стратифікації ландшафтів проводилося вченими Естонії для збереження біорізноманіття [11], моделювання майбутнього лісових ландшафтів Карпат внаслідок змін кліматичних умов -у роботі [12].…”
Section: аналіз останніх досліджень і публікаційunclassified
“…This successful method of the consistent classification of land into relatively homogenous strata has been proven to provide a valuable spatial framework as the basis for monitoring ecological indicators across large areas. There are now several examples of where the British methods have been emulated effectively, including Northern Ireland (Cooper, 2000), Spain (Elena-Rosselló, 1997), Norway (Bakkestuen et al, 2008), Sweden (Ståhl et al, 2011), Estonia (Villoslada et al, 2016) and Europe (and the whole world) (Metzger et al, 2013).…”
Section: Survey Design: Site Selection and Stratificationmentioning
confidence: 99%